PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATAN KETERAMPILAN MENULIS KARYA ILMIAH SISWA KELAS XI MM2 SMK MUHAMMADIYAH 2 PALEMBANG - Handayani, Fera; Danto, Danto; Houtman, Houtman (STKIP PGRI Bandar Lampung, 2021)
Based on the results of observation and interview that the skills of sriting scientific papers in class XI MM2 students of SMK Muhammadiyah 2 Palembang are still categorized as quite low. It still has not reached the specified minimum limit value, which is 75. The causes of the low scientific writing skills of studendts are (1) low motivation of students is learning to write scientific papers, (2) difficulty in finding problems, (3) where do students lack intereset because they do not have the problem being studied in finding solution offered by researchers to improve writing skills of scientific paperin class XI MM2 SMK Muhammadiyah 2 Palembang is by using problem –based learning media. The formulation of the problem in this study is how to improve writing skills of scientific papers in class XI MM2 SMK Muhammadiyah 2 Palembang after using a problem-based learning model. The research carried out was classroom action reseach that used two cycles namely cycle 1 and cycle 2. The data collection techniques in this study were observation, tests, interviews. The research subject uses Cluster Sampling, which is on class. The author sets one class as the research subjeck, namely class XI MM2. Based on the results of research and discussion, it can be concluded that the skills of writing scientific papers using problem-based learning media in class XI MM2 students have increased. Therefore the hypothesis proposed that the skill of writing scientific papers using problem-based learning media in class XI MM2 SMK Muhammadiyah 2 Palembang inscreased, proved to be true.